2023
DOI: 10.1097/mcc.0000000000001097
|View full text |Cite
|
Sign up to set email alerts
|

Damage control surgery: old concepts and new indications

C. Yvonne Chung,
Thomas M. Scalea

Abstract: Purpose of review While the principles of damage control surgery - rapid hemorrhage and contamination control with correction of physiologic derangements followed by delayed definitive reconstruction - have remained consistent, forms of damage control intervention have evolved and proliferated dramatically. This review aims to provide a historic perspective of the early trends of damage control surgery as well as an updated understanding of its current state and future trends. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Some studies have investigated the possibility to deploy autologous reinfusion drains for post-operative cell salvage [ 107 , 108 ]. Damage control surgery Damage control surgery (DCS) as part of damage control strategy is generally performed together with damage control resuscitation in severely bleeding patients [ 109 112 ]. DCS should be implemented as soon as its necessity is recognized [ 113 116 ].…”
Section: Intraoperative Surgical Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have investigated the possibility to deploy autologous reinfusion drains for post-operative cell salvage [ 107 , 108 ]. Damage control surgery Damage control surgery (DCS) as part of damage control strategy is generally performed together with damage control resuscitation in severely bleeding patients [ 109 112 ]. DCS should be implemented as soon as its necessity is recognized [ 113 116 ].…”
Section: Intraoperative Surgical Factorsmentioning
confidence: 99%
“…The patients are then transferred to intensive care unit to allow them to recover from the physiological derangements and to be able to face further reconstructive surgical phases. It is demonstrated that DCS helps in increasing overall survival of patients, reduces the risk of developing trauma coagulopathy and can potentially reduce the total amount of blood product usage [ 109 , 110 ]. DCS strategies may be also applied to non-traumatic emergency surgical patients.…”
Section: Intraoperative Surgical Factorsmentioning
confidence: 99%
“…Much research energy has been invested over the past two decades to develop, implement and optimize strategies and measures to early control severe bleeds and restore hemostasis in the context of severe trauma. While the principles of damage control surgery have essentially remained consistent, forms and frequency of interventions have evolved dramatically [9]. Surgical damage control is now used in conjunction with damage control resuscitation to restore physiology and prevent further collapse.…”
mentioning
confidence: 99%
“…Surgical damage control is now used in conjunction with damage control resuscitation to restore physiology and prevent further collapse. Chung and Scalea critically review this concept and highlight potential risks when being overused, in particular along with damage control laparotomy [9]; subsequently, Cioffi et al provide current evidence and guidance for the nonoperative management of blunt abdominal trauma in hemodynamically stable patients [10]. In mangled extremities where integrity and viability are in danger, the decision of primary amputation versus limb salvage becomes critical.…”
mentioning
confidence: 99%
See 1 more Smart Citation